The Influence Of Human Resources Quality And Training On Employee Performance At The Communication Of Statistics And Crimination Department Of Pekanbaru City - Ferdi Virdaus; Maza'i; Sumardin (International Journal of Business and Quality Research, 2023)
This study aims to determine the effect of the quality of human resources and training on employee performance at the Ministry of Communication and Informatics Statistics and Coding in Pekanbaru City. The method used is descriptive method. Collecting data using a list of statements or questionnaires filled out by the respondents. Then analyzed using multiple linear regression analysis.The results of multiple linear regression analysis produce a value of Y = 38.931 + 0.492X1 + 0.701X2 + e, which means that each discussion of the independent variable regression coefficient unit without adding the value of other variables, the performance increases according to the unit number of each variable. The results explain that the F test has a value of tcount ≥ttable (38,931 greater than 3.22) and a significance level of 0.000 <0.005. This means that the Quality of Human Resources and Training simultaneously has a significant effect on Employee performance.